2005
DOI: 10.1080/20786204.2005.10873232
|View full text |Cite
|
Sign up to set email alerts
|

Is pregnancy termination being used as a family planning method in the Free State?

Abstract: Background: This study determined the profile of women seeking termination of pregnancy (TOP) in the Free State and whether TOP was used as a family planning method.Methods: Seven hundred and fifty women (15-47 years old) seeking TOP at the Reproductive Health Unit of the National Hospital in Bloemfontein were included in this cross-sectional study. The women who gave verbal consent completed a questionnaire during counselling. Results:The median age of the participants was 24 years and 77.3% were single. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Several studies have reported similar race distribution when it comes to TOP, where black people remained the majority race seeking TOP compared to other races in most parts of South Africa. 10 , 12 , 13 Of interest, this study found that most women between 20 and 29 years requested TOP more than any other age groups. At this age, it is assumed that women understand the risks of engaging in unprotected sexual activity or without contraceptive use, compared with adolescents.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have reported similar race distribution when it comes to TOP, where black people remained the majority race seeking TOP compared to other races in most parts of South Africa. 10 , 12 , 13 Of interest, this study found that most women between 20 and 29 years requested TOP more than any other age groups. At this age, it is assumed that women understand the risks of engaging in unprotected sexual activity or without contraceptive use, compared with adolescents.…”
Section: Discussionmentioning
confidence: 70%
“…Similar findings have been reported locally. 7 These figures are high when compared to an earlier study conducted in Peru, where 22% (91/410) of the pregnancies was unwanted. 10 The requests for TOP in our study were influenced by financial problems, being too young, being a student, positive HIV status and insecure relationships.…”
Section: Discussionmentioning
confidence: 60%
“…Lang et al reported that more than half of the participants in their study indicated that nobody had influenced their decision to undergo TOP but the partners represented the strongest influence (23.2%), followed by the parents (11.5%). 7 A USA study reported that women were more likely to confide in their female friends about their pregnancy and decision about TOP than family members or partners. 13 In our study, despite positive attitudes of women towards abortion, 394 (61%) of the women were against having an abortion but were forced to undergo termination because of circumstances beyond their control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In the Free State, 73% of respondents did not use any contraception, and the methods that were most commonly used were the male condom, oral contraceptives and injectables. 19 In a Cape Town study, inconsistent contraceptive use, no contraception and contraceptive failure contributed to a large number of unwanted pregnancies. Problems associated with male condom use was described as a major source of contraceptive failure.…”
Section: Theme 3: Contraceptive Failurementioning
confidence: 99%